2016
DOI: 10.1111/bjh.14053
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation pattern of anti‐platelet IgG is stable during pregnancy and predicts clinical outcome in alloimmune thrombocytopenia

Abstract: Fetal or neonatal alloimmune thrombocytopenia (FNAIT) is a potentially life-threatening disease where fetal platelets are destroyed by maternal anti-platelet IgG alloantibodies. The clinical outcome varies from asymptomatic, to petechiae or intracranial haemorrhage, but no marker has shown reliable correlation with severity, making screening for FNAIT impractical and highly inefficient. We recently found IgG Fc-glycosylation towards platelet and red blood cell antigens to be skewed towards decreased fucosylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
102
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 51 publications
(62 reference statements)
13
102
0
1
Order By: Relevance
“…Two research groups recently described decreased fucosylation of anti-HPA-1a antibodies causing FNAIT, and that fucosylation may be useful to predict disease severity 104,105…”
Section: Predictors Of Clinical Outcomementioning
confidence: 99%
“…Two research groups recently described decreased fucosylation of anti-HPA-1a antibodies causing FNAIT, and that fucosylation may be useful to predict disease severity 104,105…”
Section: Predictors Of Clinical Outcomementioning
confidence: 99%
“…Although IgG produced in most human immune responses are highly fucosylated, we recently found that allogeneic immune responses against red blood cells and platelets can be skewed towards non-fucosylated IgG, the level of which correlates with disease outcome14152627. Similarly, immune responses with low-core fucosylation can also be found directed against HIV – particularly in elite controllers28.…”
mentioning
confidence: 99%
“…We recently found that IgG1‐responses against platelet antigens and RhD on RBCs can be particularly skewed towards IgG with low core‐fucosylation (Wuhrer et al , ; Kapur et al , ; Sonneveld et al , ), a feature that has only previously been described for anti‐human immunodeficiency virus (HIV) antibodies, but never for any other immune response (Ackerman et al , ). This is reflected in total serum IgG‐Fc having ~94% fucose on the glycopeptide level (Selman et al , ; Fokkink et al , ; Vestrheim et al , ).…”
mentioning
confidence: 99%